The Paradigm of Islamic Education Philosophy: Reconstructing the Values of Religious Humanism in the Era of Globalization - La Zubair (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The paradigm of Islamic education philosophy has significant relevance in addressing the challenges of globalization, which is characterized by secularization, hedonism, individualism, and moral crises that erode spiritual and humanitarian values. This research aims to examine the reconstruction of the value of religious humanism as the basis of Islamic education. The research method used is literature with a philosophical-hermeneutical analysis approach. The results of the study show that the reconstruction of Islamic education based on religious humanism can give birth to a generation of faith, knowledge, and noble character, as well as being ready to compete in the global era. The practical implications of this study emphasize the importance of integrating religious science and modern science, the development of learning methods, and educational policies that affirm the character of religious moderation. Thus, the paradigm of religious humanism in Islamic educational philosophy not only serves as a theoretical discourse but also as a practical framework in building a more humane, just, and dignified world civilization. Keywords: Islamic education, religious humanism, the era of globalization